Carry‐over effects provide linkages across the annual cycle of a Neotropical migratory bird, the Louisiana Waterthrush Parkesia motacilla. (4th February 2016) - Latta, Steven C.; Cabezas, Sonia; Mejia, Danilo A.; Paulino, Maria M.; Almonte, Hodali; Miller‐Butterworth, Cassandra M.; Bortolotti, Gary R.
Abstract : Population limitation models of migratory birds have sought to include impacts from events across the full annual cycle. Previous work has shown that events occurring in winter result in some individuals transitioning to the breeding grounds earlier or in better physical condition than others, thereby affecting reproductive success (carry‐over effects). However, evidence for carry‐over effects from breeding to wintering grounds has been shown less often. We used feather corticosterone (CORTf ) levels of the migratory Louisiana Waterthrush Parkesia motacilla as a measure of the physiological state of birds at the time of moult on the breeding territory to investigate whether carry‐over effects provide linkages across the annual cycle of this stream‐obligate bird. We show that birds arriving on wintering grounds with lower CORTf scores, indicating reduced energetic challenges or stressors at the time of moult, occupied higher quality territories, and that these birds then achieved a better body condition during the overwinter period. Body condition, in turn, was important in determining whether adult birds returned the following winter, with birds in better condition returning at higher rates. Together these data suggest a carry‐over effect from the breeding grounds to the wintering grounds that is further extended with respect to annual return rates. Very few other studies have linked conditions during the previous breeding season with latent effects during the subsequent overwintering period or with annual survival. This study shows that the effects of variation in energetic challenges or stressors can potentially carry over from the natal stream and accumulate over more than one life‐history period before being manifested in reduced survival. This is of particular relevance to models of population limitation in migratory birds.